2009
DOI: 10.4049/jimmunol.0803267
|View full text |Cite
|
Sign up to set email alerts
|

Myosin-IIA and ICAM-1 Regulate the Interchange between Two Distinct Modes of T Cell Migration

Abstract: How T cells achieve rapid chemotactic motility under certain circumstances and efficient cell surface surveillance in others is not fully understood. We show that T lymphocytes are motile in two distinct modes: a fast “amoeboid-like” mode, which uses sequential discontinuous contacts to the substrate; and a slower mode using a single continuously translating adhesion, similar to mesenchymal motility. Myosin-IIA is necessary for fast amoeboid motility, and our data suggests that this occurs via cyclical rear-me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
139
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 112 publications
(159 citation statements)
references
References 44 publications
(47 reference statements)
18
139
2
Order By: Relevance
“…By dissecting T-cell migration in vitro on chamber slides coated with different substrates (but in the absence of cognate antigen), Krummel and colleagues have identified distinct crawling modes: amoeboid walking on casein-coated surface and haptokinetic sliding on ICAM-1-coated surface (22). Interestingly, the sliding mode was shown to be associated with increased adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…By dissecting T-cell migration in vitro on chamber slides coated with different substrates (but in the absence of cognate antigen), Krummel and colleagues have identified distinct crawling modes: amoeboid walking on casein-coated surface and haptokinetic sliding on ICAM-1-coated surface (22). Interestingly, the sliding mode was shown to be associated with increased adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…A recent two-photon imaging study visualized the intraluminal crawling of encephalitogenic T cells on meningeal microvessels at a higher velocity of 12.5 mm/min in vivo (Bartholomaus et al, 2009). However, in vitro studies of T cell crawling on immobilized ICAM-1 under static conditions (Jacobelli et al, 2009;Smith et al, 2005) documented highly variable T cell crawling velocities that ranged from 4 to 9 mm/min. In particular, the density of ICAM-1 on the crawling substrate (Smith et al, 2005) or the interplay between T cell adhesion and its actomyosin contractility during crawling (Jacobelli et al, 2009) were definitely shown to influence the speed of movement.…”
Section: Discussionmentioning
confidence: 99%
“…However, in vitro studies of T cell crawling on immobilized ICAM-1 under static conditions (Jacobelli et al, 2009;Smith et al, 2005) documented highly variable T cell crawling velocities that ranged from 4 to 9 mm/min. In particular, the density of ICAM-1 on the crawling substrate (Smith et al, 2005) or the interplay between T cell adhesion and its actomyosin contractility during crawling (Jacobelli et al, 2009) were definitely shown to influence the speed of movement. Thus, different velocities of T cell crawling on brain endothelial cells could be caused by variations in the spatial organization of endothelial cell adhesion molecules.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, TCR signaling inactivates the contractile machinery necessary for rapid motility by phosphorylating myosin IIA (Jacobelli et al, 2004). Upon myosin IIA inhibition or depletion, T cells maintain an active lamellipodium and slide along in a slow, actin protrusion-dependent mode of motility (Jacobelli et al, 2009). This mode of slow motility during TCR signaling might serve to ensure that the T cell can detect and integrate as many antigen signals as possible by probing as large of an antigen-presenting surface as possible.…”
Section: Reagents Antibodies and Flow Cytometrymentioning
confidence: 99%